Enzymatic processing of bioactive glycosides from natural sources - Weignerová, Lenka; Kren, Vladimír (Topics in current chemistry, 2010)
A number of biologically active natural products are glycosides. Often, the glycosidic residue is crucial for their activity. In other cases, glycosylation only improves their pharmacokinetic parameters. Enzymatic modification of these glycosides - both extension of the glycoside moiety and its selective trimming - is advantageous due to their selectivity and mildness of the reaction conditions in the presence of reactive and sensitive complex aglycones. Enzymatic reactions enable the resulting products to be used as "natural products", e.g., in nutraceuticals. This chapter concentrates on naturally occurring glycosides used in medicine but also in the food and flavor industry (e.g., sweeteners). Both "classical" and modern methods will be discussed.
Keywords: Food; glykosidy; biologické přípravky; Glycosides; Antineoplastic Agents; protinádorové látky; antibakteriální látky; Anti-Bacterial Agents; Biological Products; Glycosylation; potraviny; glykosylace